Improving students' vocabulary mastery through picture cards - Makaruku, Hendrik (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2021)
This study aims to improve the vocabulary mastery of VII grade students of SMP Negeri 4 Taniwel, West Seram, Mollucas, through the use of picture cards. This research was classroom action research. The research subjects were grade VII students of SMP Negeri 4 Taniwel, West Seram, Mollucas, consisting of 24 students. The techniques for collecting the data were observation and interview, whereas the instruments for collecting data were observation checklists, field notes, and tests. The data analysis using qualitative analysis and quantitative analysis. The qualitative analysis was related to the result analysis of the observation, interview, field notes, and observation checklist, while the quantitative analysis was related to the analysis process of simple statistics from the students' test results. The result of the research indicates that the use of picture cards can improve the students' vocabulary mastery, as shown by the students' test results that improved in each cycle. The students' vocabulary mastery was said